The European Social Model: Lessons for Developing Countries - Assar Lindbeck (Asian Development Bank (ADB), 2002)
"Developing countries, in particular the least developed ones, probably have more to learn from social policies in Europe during the early 20th century than from the elaborate welfare-state arrangements after World War II. In addition to macroeconomic growth and stability, the main ambitions must be to fight human deprivation, including illiteracy, malnutrition, and poor access to water and sanitation; in some cases, also weak, incompetent, and/or corrupt governments. It is also important that informal systems in the fields of transfers and social services are not destroyed when developing countries embark on more formal systems in these fields in the future. The European experience also warns against the creation of social systems that are so generous that disincentives, moral hazard, and receding social norms seriously distort the national economy, including the labor market"
hdl:11540/1932
Keywords: 330; EU-Sozialpolitik; EU-Staaten